Corporate Dividend Policy: A Study of Commercial Banks of Nepal - Bhandari, Bina; Pokharel, Trilochan (Administration and Management Review, 2012)
Dividend policy is the policy used by a company to decide how much it will pay out to shareholders in dividends. Taking financial indicators of 8 commercial banks for the period of 1996/97 to 2006/07, this study attempts to elucidate the dividend practices of commercial banks of Nepal. Abound by controversies and unpredictability, this study concludes that commercial banks of Nepal do not show uniform trend of dividend policy. Dividend policy practiced by commercial banks of Nepal is neither fully explained by residual theory nor stable theory. With the development of financial institutions in Nepal, they need to follow a robust method of dividend policy so that investors can predict stock market and make a rationale investment decision. Administrative and Management Review Vol. 24, No. 2, August 2012, Page 24-44